Integrated Role of Row Spacing and Adjuvant to Reduce Herbicide Dose in Maize Under Semi-Arid Conditions - NADEEM,M.A. (2018)
ABSTRACT: Crop row spacing adjustment and adjuvants have a significant role in decreasing herbicide cost and environmental damage by reducing herbicide application rate. A field study was conducted to assess the impact of two row spacing values and reduced herbicide rates along with adjuvant on weeds in maize in 2014 and 2015. The experiment consisted of atrazine plus mesotrione plus halosulfuran methyl (pre-mixed herbicide) at label rate (719.2 g a.i. ha-1); reduced rates of 75% (539.4 g a.i. ha-1) and 50% (359.6 g a.i. ha-1) alone and in combination with alkyl ether sulphate at 396.8 mL ha-1 as an adjuvant along with weedy check in maize sown at 60 and 75 cm row spacing. Alkyl ether sulphate increased weed control efficacy (13-35%) of the pre-mixed herbicide. Herbicide along with adjuvant provided effective weed control at 60 cm as compared to 75 cm apart sown maize. The most effective control of weeds, and increase in maize grain yield (33-45% as compared to non-treated control) and net income were obtained by the pre-mixed herbicide at 539.4 g a.i. ha-1 (75% of recommended rate) with adjuvant and pre-mixed herbicide at 719.2 g a.i. ha-1 (recommended dose) without adjuvant. The results revealed that the rate of pre-mixed herbicide can be reduced by up to 25% of the recommended field rate by the addition of alkyl ether sulphate as an adjuvant at 60 cm row spacing of maize to increase maize yield and net income.